Adaptor protein 1 B mu subunit does not contribute to the recycling of kAE1 protein in polarized renal epithelial cells. (17th February 2017) - Almomani, Ensaf Y.; Touret, Nicolas; Cordat, Emmanuelle
Abstract: Mutations in the gene encoding the kidney anion exchanger 1 (kAE1) can lead to distal renal tubular acidosis (dRTA). dRTA mutations reported within the carboxyl (C)-terminal tail of kAE1 result in apical mis-targeting of the exchanger in polarized renal epithelial cells. As kAE1 physically interacts with the μ subunit of epithelial adaptor protein 1 B (AP-1B), we investigated the role of heterologously expressed μ1B subunit of the AP-1B complex for kAE1 retention to the basolateral membrane in polarized porcine LLC-PK1 renal epithelial cells that are devoid of endogenous AP-1B. We confirmed the interaction and close proximity between kAE1 and μ1B using immunoprecipitation and proximity ligation assay, respectively. Expressing the human μ1B subunit in these cells decreased significantly the amount of cell surface kAE1 at the steady state, but had no significant effect on kAE1 recycling and endocytosis. We show that (i) heterologous expression of μ1B displaces the physical interaction of endogenous GAPDH with kAE1 WT supporting that both AP-1B and GAPDH proteins bind to an overlapping site on kAE1 and (ii) phosphorylation of tyrosine 904 within the potential YDEV interaction motif does not alter the kAE1/AP-1B interaction. We conclude that μ1B subunit is not involved in recycling of kAE1.